Amelioration of bleomycin-induced epithelial-mesenchymal transition in pulmonary fibrosis by baicalein in mice (Indian Journal of Veterinary Pathology, 2025)
Epithelial-mesenchymal transition (EMT) play a vital role in pulmonary fibrosis. The present study investigates the ameliorative effect of baicalein, a bioactive flavonoid present in the dry roots of Scutellariabaicalensis Georgi, on bleomycin-inducedpulmonary fibrosis and subsequent EMT. Mice were given a single intratracheal instillation of saline containing bleomycin @ 1 mg/kg b.wt. Baicalein in different doses of 0.1, 1.0 and 10 mg/kg b.wt was given intraperitoneally daily for 8 weeks. Baicalein was effective in attenuating the BLM induced Pulmonary fibrosis through suppression of oxidative stress, inflammation, histological as well as ultrastructural damages and EMT, especially during the chronic stage injury. This study will provide additional knowledge on the ameliorative effect of baicalein during the later stages of lung injury where the EMT starts and this may help in the therapeutic or management of clinical chronic lung injury associated pulmonary fibrosis.